Nitric Oxide Is Locally Produced in the Human Middle Ear and Is Reduced by Acquired Cholesteatoma. Issue 2 (25th October 2021) - Westerberg, Johanna; Granath, Anna; Drakskog, Cecilia; Tideholm, Ellen; Kumlien Georén, Susanna; Weitzberg, Eddie; Cardell, Lars-Olaf
Abstract : Objective: To find out if nitric oxide (NO) can be locally produced in the middle ear and if chronic otitis media (COM) and acquired cholesteatoma affect the production. Design: Case-control study. Setting: Two tertiary-referral hospitals. Patients: Gaseous NO from 11 patients with unilateral perforations or grommet openings was measured with chemiluminescence. Middle ear mucosa from 48 patients with COM and 26 patients with cholesteatoma was investigated. Main Outcome Measures: Detection of NO. Expression of nitric oxide synthase (NOS) mRNA, in mucosa from COM, cholesteatoma and healthy controls, quantified using polymerase chain reaction. Results: The gaseous NO from ears with a unilateral tympanic membrane perforation or a grommet was higher (9 ± 3 ppb, n = 11) than among the controls (4 ± 1 ppb, n = 11, p  = 0.04). Lower levels of eNOS (2.64 ± 0.86 mol/100, 000 mol ACTB) were detected in the pooled samples from the COM group (n = 48), compared with the control group (140.48 ± 92 mol/100, 000 mol ACTB, n = 45, p  = 0.010). In the cholesteatoma group (n = 26), a lower expression of nNOS (5.78 × 10 −6  ± 1.13 × 10 −6 ΔCt) was found in comparison with the controls (1.23 × 10 −4  ± 3.18 × 10 −5 ΔCt, n = 15, p  = 0.011). Conclusions: NO is likely a natural and permanent part of the gas mixture in the human middle ear. The presence of NOS enzymes in the middle ear mucosa indicates an ongoing NO production and the reduction of NOS in ears with cholesteatoma, and pooled samples from ears with COM, suggest a role for locally produced NO in middle ear disease.